Japan's Failed Revolution: Koizumi and the Politics of Economic Reform - George Mulgan, Aurelia (ANU Press, 2013)
Japan's Failed Revolution: Koizumi and the Politics of Economic Reform asks why, despite all the high expectations, the Japanese public's desire for economic reform, and leadership of a majority coalition in a parliamentary democracy, the reformer Prime Minister Koizumi has not achieved the economic reforms expected of him since he surprisingly attained power over a year ago. To unravel this 'puzzle', Aurelia George Mulgan eschews the simplicities of both cultural and rational choice explanations and systematically tests the propositions in the comparative literature on 'failed reform'. The result is one of the best books ever written about contemporary Japanese politics. It explains how, despite British-style parliamentary institutions, Japan's very 'un-Westminster' traditional policymaking process involving the ruling party and the bureaucracy's structure and linkage has stymied and will probably continue to stymie even a sincere and active Prime Minister's best reform intentions. This book should be read by all political scientists, journalists, economists, and students interested in contemporary Japan. Ellis S. Krauss Graduate School of International Relations and Pacific Studies University of California, San Diego. The author takes a scalpel to dissect Japan's dysfunctional political system. She shows with wonderful clarity and depth of knowledge why the Koizumi reforms are not succeeding, and why revolutionary political change is needed as a precondition for economic recovery. The book should be required reading for anyone involved with contemporary Japan. J.A.A. Stockwin University of Oxford.